Экспертная оценка необходимого времени эвакуации людей - Polevoda Иван; Makarov Евгений; Demenchuk Александр; Osyaev Владимир (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
The expert evaluation method for evacuation procedures based on time-rate of maximum allowable fire factors content is represented.